2006
DOI: 10.1002/art.22172
|View full text |Cite
|
Sign up to set email alerts
|

IK cytokine ameliorates the progression of lupus nephritis in MRL/lprmice

Abstract: Objective. IK cytokine has been isolated as a factor that inhibits interferon-␥ (IFN␥)-induced expression of class II major histocompatibility complex (MHC) antigens. Aberrant expression of class II MHC antigens has reportedly been recognized in the target organs of autoimmune diseases and been associated with disease activity. In this study, we investigated whether IK cytokine can ameliorate the progression of lupus nephritis in MRL/lpr mice. Methods. A truncated IK analog was prepared and transfected into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 39 publications
4
32
0
Order By: Relevance
“…S2A). These data are consistent with previous studies (33,49). We also identified a reduction in the mRNA levels of other MHC class II accessory molecules, Ii chain and HLA-DM, with the quantitative real-time RT-PCR analysis of tIK-transfected Raji B cells at 24-48 h after transfection ( Supplementary Fig.…”
Section: Cvb3 Infection Transiently Increased Ik Expression and Reducsupporting
confidence: 94%
See 4 more Smart Citations
“…S2A). These data are consistent with previous studies (33,49). We also identified a reduction in the mRNA levels of other MHC class II accessory molecules, Ii chain and HLA-DM, with the quantitative real-time RT-PCR analysis of tIK-transfected Raji B cells at 24-48 h after transfection ( Supplementary Fig.…”
Section: Cvb3 Infection Transiently Increased Ik Expression and Reducsupporting
confidence: 94%
“…Therefore, we used this cell line as the endogenous-IKgene-negative cells to analyze the role of IK. A previous study showed that truncated IK (tIK), encoded by a 0.72-kb fragment of IK (residues 316-557), is functional in transfected cells (33). Furthermore, the treatment with exogenous tIK protein caused a reduction in IFNc-induced MHC class II expression in murine macrophage cell lines (33).…”
Section: Cvb3 Infection Transiently Increased Ik Expression and Reducmentioning
confidence: 98%
See 3 more Smart Citations